INFLUENCE OF LEADERSHIP EXPERIENCE ON THE DEVELOPMENT OF MULTI-SERVICE BUSINESS IN A COMPETITIVE MARKET - Meri Dilbaryan (Scholar Express Journals, 2025)
The article examines the role of leadership experience in the development of multi-service companies operating in a highly competitive environment. Theoretical approaches to leadership, its impact on strategic management, innovation and integration of services are considered. Based on the analysis of practical cases, it is shown that the presence of experience in managing different service areas by a manager increases the company's ability to quickly adapt, expand the product portfolio and form sustainable customer trust.
Keywords: multi-service business; Leadership; competitive market